Chloride diffusivity and mechanical performance of UHPC with hybrid fibers under heat treatment regime. (March 2021) - Pourjahanshahi, Amin; Madani, Hesam
Abstract: Steel fibers are an inseparable part of ultra high performance concretes (UHPC). The effects of steel fibers have been widely studied in recent years; however, the hybridization of steel fiber with different types of fibers and their effect on the properties of UHPC has not been completely investigated. In addition, under thermal treatment, which is a common way for curing UHPC elements, the use of hybrid fibers may change the concrete characteristics. In this paper, mixtures containing different types of fibers in the hybrid forms were produced and the specimens were cured under normal and heat curing conditions. To characterize the effect of hybrid fibers on UHPC mixes under different curing regimes, the workability, compressive strength, flexural parameters (including first crack strength, module of rupture, load-deflection curves and toughness index) and scanning electron microscope (SEM) microstructural analyses were investigated. The results revealed that the concrete mix with 2.5 % mono fiber had higher flexural performance than the hybrid mixes. However, the use of steel fiber with the volume fraction of 1.5 % was more effective in improving the compressive strength. Higher flexural load-bearing capacity was observed for the hybrid mixes with macro fibers of Barchip and Kortta. The UHP-FRCs containing Barchip and Kortta fibers, due to the permeable internal structure, had lower chloride resistance than the 2.5 % of steel fiber concrete. In addition, the chloride migration coefficients of the hybrid mixtures with the glass, carbon and polypropylene fibers were about 5 times higher than those of the mix with 1.5 % steel fiber. Compared with normal curing condition, the load drop after cracking was more visible for the mixes cured under heat curing, which could be limited by using high-volume steel fiber and hybrid micro fibers. Furthermore, applying thermal treatment for curing concrete mixes led to lower chloride ion penetration; the enhancement was more pronounced for the hybrid mixes with micro fibers of glass, carbon and polypropylene.